2014
DOI: 10.1002/dvg.22762
|View full text |Cite
|
Sign up to set email alerts
|

Natural reversal of left‐right gut/gonad asymmetry in C. elegans males is independent of embryonic chirality

Abstract: Anatomical left-right (L/R) handedness asymmetry in C. elegans is established in the four-cell embryo as a result of anteroposterior skewing of transverse mitotic spindles with a defined handedness. This event creates a chiral embryo and ultimately an adult body plan with fixed L/R positioning of internal organs and components of the nervous system. While this “dextral” configuration is invariant in hermaphrodites, it can be reversed by physical manipulation of the early embryo or by mutations that interfere w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Coordination among these axes is critical as any misinterpretation could lead to severe birth defects 4, 22, 33 . On a 2D substrate, cell migration direction is directly linked to the back-front (BF) polarity through the polarized shape that migrating cells take on 14, 21, 30, 41, 44, 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Coordination among these axes is critical as any misinterpretation could lead to severe birth defects 4, 22, 33 . On a 2D substrate, cell migration direction is directly linked to the back-front (BF) polarity through the polarized shape that migrating cells take on 14, 21, 30, 41, 44, 49 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the L/R gut/gonad asymmetry in N2 males raised at 25°C is frequently (more than 5%) reversed [40], with the fully developed gut occupying the position on the right normally taken by the gonad (figure 1). These reversals do not appear to reflect a complete inversion of L/R anatomy, as a marker of the right-specific ASER neuron is expressed in its normal position on the right [34].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, viable sinistral animals can arise as a result of mutations in gpa-16 [17], which encodes a small rho-GTPase required for normal spindle placement, and in the actin cytoskeleton [32], leading to reversal of AB spindle skewing. However, several studies of a large number (more than 15 000) of animals [17,35,40,42] reared at 208C indicated that such L/R left-right reversals in the arrangement of the major organs in the laboratory N2 isolate do not occur under normal conditions, suggesting that evolutionary constraints have led C. elegans to adopt a virtually invariant dextral body plan. We previously reported that the L/R gut/gonad asymmetry in N2 males raised at 258C is frequently (more than 5%) reversed [40], with the fully developed gut occupying the position on the right normally taken by the gonad (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations